2021
DOI: 10.1002/anie.202104217
|View full text |Cite
|
Sign up to set email alerts
|

AgII‐Mediated Electrocatalytic Ambient CH4 Functionalization Inspired by HSAB Theory

Abstract: Although most class (b) transition metals have been studied in regardt oC H 4 activation, divalent silver (Ag II ), possibly owing to its reactive nature,isthe only class (b) highvalent transition metal center that is not yet reported to exhibit reactivities towards CH 4 activation. We now report that electrochemically generated Ag II metalloradical readily functionalizes CH 4 into methyl bisulfate (CH 3 OSO 3 H) at ambient conditions in 98 %H 2 SO 4 .M echanistic investigation experimentally unveils al ow act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Reproduced with permission. [167] Copyright 2021, Wiley-VCH. A flow of CH 4 /O 2 -saturated water (15 mL h −1 ) is passed through a packed layer of metal-organic-framework immobilized with mono-iron hydroxyl sites [PMOF-RuFe(OH)], achieving 100% selectivity for methanol production with a production rate of 8.81 ± 0.34 mmol g cat −1 h −1 , surpassing the activity of methane monooxygenase (Figure 16d).…”
Section: Advanced Reactor Designmentioning
confidence: 99%
“…Reproduced with permission. [167] Copyright 2021, Wiley-VCH. A flow of CH 4 /O 2 -saturated water (15 mL h −1 ) is passed through a packed layer of metal-organic-framework immobilized with mono-iron hydroxyl sites [PMOF-RuFe(OH)], achieving 100% selectivity for methanol production with a production rate of 8.81 ± 0.34 mmol g cat −1 h −1 , surpassing the activity of methane monooxygenase (Figure 16d).…”
Section: Advanced Reactor Designmentioning
confidence: 99%
“…The recent studies showed that methane, with its extremely high ionization potential of 12.6 eV, may be electrochemically activated in sulphuric acid in the presence of Ag salts [116] . However, the current yield of this process, leading to methyl hydrogensulphate, is immensely small and it is unclear how it might be improved.…”
Section: Properties Of Silver and Its Compoundsmentioning
confidence: 99%
“…The direct conversion of methane (CH 4 ) to easily transportable liquid fuels or value-added chemical feedstocks is a topic of great interest for the natural gas industries. However, it remains one of the grand challenges in the area of energy utilization and catalysis science due to the high C–H bond strength (Δ H C–H = 104 kcal mol –1 ) and perfect tetrahedral symmetry with four equivalent C–H bonds of CH 4 . The typical nonoxidative conversion of CH 4 usually occurs above 600 °C with shortcomings of coke formation on the catalyst and low selectivity of desired products as well as high energy consumption. , By contrast, direct partial oxidation of CH 4 to oxygenates by reactive oxygen species can usually proceed at temperatures below 200 °C. Nevertheless, reactive oxygen species are usually obtained under harsh conditions, such as using corrosive or expensive oxidants (fuming sulfuric acid, nitrous oxide, ozone, or hydroperoxide). The electrochemical process provides an alternative for C–H bond dissociation even at room temperature via the application of an additional voltage. ,, Much effort has been devoted to the electrocatalytic CH 4 oxidation at the anode with corrosive and oxidative overpotentials generally higher than 1.5 V versus reversible hydrogen electrode (vs RHE), which, however, is up against the great challenge on the delicate control of the competing reactions of the electrochemical oxygen evolution reaction. , …”
Section: Introductionmentioning
confidence: 99%